2021
DOI: 10.1016/j.sjbs.2021.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Developing specific leaf promoters tools for genetic use in transgenic plants towards food security

Abstract: Significant yields enrichments are necessitated for meeting the rapid global growth population together with the expected demanding for food, particularly major crops. Photosynthesis improvement is an unexploited opportunity in research on improving crop yields. However, the lack of sufficient molecular promoters tools leads to the need to explore and analyze native leaf-specified promoters for manipulating photosynthesis activities in plants. Two B. distachyon promoters, sedoheptulose-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Similarly, the rice SBPase gene also shows a leaf-specific expression pattern [ 41 ]. Previous studies have shown that the promoters of genes specifically expressed in leaf tissues can be used to achieve the directional expression of target genes in leaf tissues [ 47 ]. For example, the promoters of the key enzymes SBPase and fructose-1,6-bisphosphatase aldolase (FBPA) in the Calvin cycle can be used to achieve the specific expression of target genes in leaf mesophyll cells [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the rice SBPase gene also shows a leaf-specific expression pattern [ 41 ]. Previous studies have shown that the promoters of genes specifically expressed in leaf tissues can be used to achieve the directional expression of target genes in leaf tissues [ 47 ]. For example, the promoters of the key enzymes SBPase and fructose-1,6-bisphosphatase aldolase (FBPA) in the Calvin cycle can be used to achieve the specific expression of target genes in leaf mesophyll cells [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the promoters of genes specifically expressed in leaf tissues can be used to achieve the directional expression of target genes in leaf tissues [ 47 ]. For example, the promoters of the key enzymes SBPase and fructose-1,6-bisphosphatase aldolase (FBPA) in the Calvin cycle can be used to achieve the specific expression of target genes in leaf mesophyll cells [ 47 ]. This study found that GhSBPase was a gene specifically expressed in leaf tissues, indicating that the promoter of this gene may also be important in achieving the directional expression of target genes in leaf tissues.…”
Section: Discussionmentioning
confidence: 99%
“…For example, CDR engineering involves the modification of plant form, such as changing root architecture with less nodal root number and more deep roots in maize [ 176 ], which requires precise control of gene expression by tissue-specific promoters [ 177 ]. Leaf-specific promoters [ 178 ] can be used for driving the expression of genes involved in CO 2 fixation; phloem tissue-specific promoters [ 179 ] can be used for genes involved in phloem-mediated translocation of sugars; and root-specific promoters [ 180 , 181 ] can be used for genes involved in root growth and development. Besides tissue-specific promoters, cell-type-specific promoters [ 182 , 183 ] can be used for high-precision control of the spatial expression pattern of CDR-related genes,…”
Section: Discussionmentioning
confidence: 99%